2021
DOI: 10.5194/acp-21-8341-2021
|View full text |Cite
|
Sign up to set email alerts
|

Significant contrasts in aerosol acidity between China and the United States

Abstract: Abstract. Aerosol acidity governs several key processes in aerosol physics and chemistry, thus affecting aerosol mass and composition and ultimately climate and human health. Previous studies have reported aerosol pH values separately in China and the United States (USA), implying different aerosol acidity between these two countries. However, there is debate about whether mass concentration or chemical composition is the more important driver of differences in aerosol acidity. A full picture of the pH differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 76 publications
1
17
2
Order By: Relevance
“…However, even those works on real-world aerosols used the diluted extracts of filtercollected samples for aerosol generation where the constituent concentration differed from pristine atmosphere aerosols. Recent out-field studies have reported the high acidity found in many ambient aerosol particles [20][21][22][23][24][25]. Thus, it is imperative to detect the LLPS in microdroplets at their pristine state, that is, in acidic environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, even those works on real-world aerosols used the diluted extracts of filtercollected samples for aerosol generation where the constituent concentration differed from pristine atmosphere aerosols. Recent out-field studies have reported the high acidity found in many ambient aerosol particles [20][21][22][23][24][25]. Thus, it is imperative to detect the LLPS in microdroplets at their pristine state, that is, in acidic environment.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with previous studies (Ding et al, 2019;Shi et al, 2017) that have demonstrated the role of NVCs in aerosol acidity. However, other studies found that NVCs have limited impacts on aerosol pH, which may be due to the relatively minor contribution of crustal ions on aerosol mass in their cases (Liu et al, 2017;Zheng et al, 2020;Zhang et al, 2021). Furthermore, the mass fraction of sulfate declines from clean periods (0.16) to light and moderate pollution periods (0.08), then slightly increases during heavy pollution periods (0.10).…”
Section: Driving Factors Of the Temporal Pm 25 Ph Variation In Beijin...mentioning
confidence: 95%
“…In addition to Ca 2+ and Na + (i.e., the NVCs) abundances, NH 3 is also an important alkaline component and plays an essential role in aerosol pH by neutralizing acidic components (H 2 SO 4 and HNO 3 ) to form particulate sulfate and nitrate and thus driving NH 3 towards to the particle phase (S. Zheng et al, 2020;Zhang et al, 2021). After doubling NH 3 emissions, the response in PM 2.5 pH is not as large as that to NVCs.…”
Section: Sensitivity To Nh 3 Emissionsmentioning
confidence: 99%
“…However, even in the presence of a large amount of NH 3 , particulate matter in China remains acidic, which will promote the catalytic effect of transition metals. Zhang et al [26] conducted a comprehensive assessment of aerosol acidity in China and America, using extended ground-level measurements and regional-scale air quality model simulations. They found that the pH values of aerosols in China are 1-2 units higher than those in America, which caused by the higher fraction of total ammonia (gas + particle) in the aerosols.…”
Section: Characteristics Of Secondary Pollution During Observation Pe...mentioning
confidence: 99%